A composite index of leading indicators of unemployment in Nigeria. Issue 1 (2nd January 2016) - Tule, Moses; Ajilore, Taiwo; Ebuh, Godday
Abstract: The study computes a composite index of leading indicators of the unemployment rate in Nigeria following the Organization for Economic Co-operation and Development (OECD) system of composite leading indicators methodology as enunciated in Gyomai and Guidetti (2012). Prediction is based on the analysis of multiple series covering diverse aspects of economic activity, which have a leading relationship to unemployment. The leading properties were determined by their cross-correlation structure and Granger Causality analyses. Once selected, the series were aggregated into single composite indicator based on the outcomes of the cross-correlation and Granger Causality estimations. The results from both the cross-correlation and Granger Causality based composite indexes provide accurate tracking of the unemployment turning points in Nigeria over a 7-year period (2008–14).